PERBANDINGAN METODE EKSTRAKSI TERHADAP KANDUNGAN LIMONIN PADA EKSTRAK METANOL BIJI JERUK SAMBAL (Citrus microcarpa Bunge) (COMPARISON OF EXTRACTION METHODS FOR LIMONIN CONTENT IN METHANOL EXTRACT OF SEEDS OF Citrus microcarpa Bunge) - Nurhaliza Nurhaliza Nurhaliza; Rudiyansyah Rudiyansyah; Harlia Harlia (Indonesian Journal of Pure and Applied Chemistry, 2022)
Limonin is a limonoid compound belonging to a terpenoid and it is found in Citrus plants including in the seeds of C. microcarpa. According to literature, limonin has been isolated by different methods from various Citrus plants with variable concentration. In this study, three extraction methods, maceration, soxhletation, and sonication were compared to examine a limonin concentration from the seeds of C. microcarpa. The purpose of this study is to determine the best extraction method which is able to give the highest concentration of limonin in the methanol extract. On the basis of phytochemical screening with the Liebermann-Burchard reagent and TLC data, it was found that the extracts from maceration, soxhletation, and sonication were positive for the triterpenoid. Further, based on the quantitative analysis, the average concentration of terpenoids obtained from the maceration, soxhletation, and sonication were 55.329%, 75.413%, and 83.473%, respectively. In conclusion, a sonication is the best method to extract a limonin by using terpenoid content.